Mengaplikasikan Ilmu Sosial Profetik dalam Pendidikan Islam - Fahmi Syaefudin; Maksudin, Maksudin (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
This article discusses applying social and professional education to islamic education. The problems of islamic education today add to the importance of emphasis and application of the social sciences of kuntowijoyo. Islamic education nowadays is a mere formality and tends to lose its own value in education. Discussion is based on experience and data from the field described and linked to library research on kuntwijoyo's professional social sciences. The discussion is elaborated on what kuntowijoyo thought about social science and its key elements. Then it is explained how the application of social and professional education in islamic education and what steps it takes. The conclusion of this study is that islamic education by applying social and professional education is that of islamic education that instilling values of faith and moral values such as empathy, empathy, and so on. The value of professional education is made into an effort to create a loving, tolerant, tolerant islamic education, virtue, respect for differences and other humanitarian attitudes.